Pengaruh Nilai Pelanggan dan Kualitas Layanan Terhadap Loyalitas Pelanggan, Melalui Kepuasan Pelanggan Pada Pelanggan Bus Efisiensi (Studi PO Efisiensi Jurusan Yogyakarta-Cilacap) - Mardikawati Woro; Farida Naili (Universitas Diponegoro, 2013)
This research is conducted to determine the influence of customer value and service quality to customer loyalty, through customer satisfaction of Bus Efisiensi. The location of this research is the reservations in Ambarketawang Gamping, Yogyakarta. The population is all passengers of Bus Efisiensi. The sample is passengers who meet the criteria as customers who have used the Bus Efisiensi more than 3 times in the past 3 months by as many as 100 respondents.The sampling technique used is purposive sampling. The analysis used in this research is the Sructural Equation Modeling (SEM). The results of this study are: (1) respondents are satisfied with the bus service; (2) PO Efisiensi has provided better quality of service; (3) respondents who are satisfied will provide the foundation for their long-term relationship to the company; (4) the customer will form expectations about the value and act on it, and they evaluate offers; (5) service quality has a positive influence on customer loyalty through customer satisfaction.